Essen in der Vielfalt – Esskultur und Nahrungszubereitung - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung)

SoTL und Forschung in der Religionspädagogik: Eine exemplarische Analyse des Zusammenhangs von Fach und der Beforschung von Fachlehre - Reis, Oliver (Scholarship of Teaching and Learning und disziplinäre Forschung: Eine komplexe Beziehung,)

Konzept und Wirkungen eines Lehrmoduls zur demokratischen Erarbeitung von Beurteilungskriterien in bildungswissenschaftlichen Seminaren des Lehramtsstudiums - Wehde, Janis

Was hat das mit mir zu tun?

Statistics and data science education as a vehicle for empowering citizens – short summary of a survey - Biehler, Rolf; Kawakami, Takashi; Lampen, Erna; Weiland, Travis; Zapata-Cardona, Lucía (European Mathematical Society Magazine)
This article is a short summary of the report of survey team 3, presented to the 15th International Congress on Mathematical Education (ICME-15) in Sydney in July 2024.

Transcription in Computing Education Research: A Review and Recommendations - Terfloth, Lutz; Lohmer, Vivien; Kern, Friederike; Schulte, Carsten (Informatics in Education)
Transcripts play a crucial role in qualitative research in computing education, with significant implications for the credibility and reproducibility of findings. However, unreflective and inconsistent transcription standards may unintentionally introduce biases, potentially undermining the validity of research outcomes and the collective progress of the field. In this article, we introduce transcription as a theoretically guided process rather than a mere preparatory step, illustrating its role using a case example. Additionally, through a systematic review of 107 qualitative research articles in computing education, we identify widespread shortcomings in the reporting and implementation of transcription practices, revealing a need for greater intentionality and transparency. To address these challenges, we propose a three-step framework for selecting, applying, and documenting transcription standards that align with the specific context and goals of a study. Rather than advocating for overly complex, one-size-fits-all transcription strategies, we emphasize the importance of a context-appropriate approach that is clearly communicated to foster trust and reproducibility. By advancing a more robust transcription culture, this work aims to support computing education researchers in adopting standards that enhance the quality and reliability of qualitative research in the field.

A New Framework for the Analysis of Media Systems and Media Organisations - Fuchs, Christian (Communication and the Public)
The article resulted in Christian Fuchs being awarded Communication and the Public’s Award for Excellence.

Erzählen von Europa - Fluchtmigration in den Romanen "Das Kontingent", "Havarie" und "Gehen, ging, gegangen" - Müller, Inez (Deutsche Griechenland-Diskurse und Griechisch-Deutscher Kulturtransfer)
Keywords: Flucht; illegale Fluchthilfe; Humanität

Zwei Perspektiven auf den Übergang in ein Studium: eine imaginäre Diskussion zwischen Wirtschaftspädagogik und Soziologie - Sloane, Hannah Sabrina (bwp@)

Dreiecke spiegeln. Herstellen und Untersuchen achsensymmetrischer Figuren - Wallner, Melina (Mathematik differenziert)

Bewegung, Spiel und Sport im Ganztag an Grundschulen – Eine qualitative Interviewstudie zur Perspektive von pädagogischem Personal und Kindern Movement, play and sport in all-day primary schools—a qualitative interview study from the perspective of pedagogical staff and children - Noetzel, Ida; Kaufmann, Nils; Neuber, Nils; von Plettenberg, Elisabeth; Satzinger, Nicole; Schröder, Stefan; Süßenbach, Jessica; Kehne, Miriam (Forum Kinder- und Jugendsport)
Zusammenfassung Kinder verbringen zunehmend mehr Zeit in öffentlichen Bildungseinrichtungen. Eine zentrale Bildungsinstitution ist die Ganztagsgrundschule. Die dortige Planung und Umsetzung von Bewegung und Sport ist bisher nur punktuell beforscht. Es mangelt unter anderem an Befunden aus der Sicht der verschiedenen Akteur*innen sowie an Kenntnissen zur bewegungsbezogenen Qualifikation des Personals. Im Rahmen der vorliegenden Teilstudie des Projektes „Move For Health“ werden diese Desiderate aufgegriffen. Die Untersuchung erfolgte mittels qualitativer Interviews an acht Ganztagsgrundschulen. Es wurden 52 Interviews mit insgesamt 140 Personen durchgeführt. Diese setzen sich aus acht Fokusgruppeninterviews mit im Ganztag tätigem Personal sowie 44 Interviews mit Kindern der dritten und vierten Klasse zusammen. Die Resultate zeigen, dass Bewegung übergreifend in unterschiedlichen Inszenierungen stattfindet und auch von den Akteur*innen als wesentlich erachtet wird. Grundsätzlich sehen alle Befragten die Relevanz von Bewegung, benennen jedoch konkrete Bedarfe und Wünsche, die sich sowohl auf Räume und Materialen als auch auf Wissen und Kompetenzen (bspw. im methodisch-didaktischen Bereich) beziehen. Kinder artikulieren im pädagogischen Spannungsfeld von Gegenwartserfüllung und Zukunftsperspektive vielfältige Bedürfnisse und Ideen zur Ausgestaltung. Dem Personal mangelt es häufig an Kompetenzen im methodisch-didaktischen Bereich oder an Wissen über das Thema Sicherheit, um die Bewegung entsprechend zu inszenieren.

Der Deutschtreff (Universität Paderborn) - Hüllweg, Julia; Blachut, Alisa (Atlas der Hochschullernwerkstätten. Ein (un-)vollständiges Kompendium.)

Mastering Temporal Challenges – Zeitwohlstand und Zeiterleben iranischer Studierender in Deutschland - Philipper, Matthias (Geschlecht und Gerechtigkeit)

Kollegiales Feedback in der Hochschullehre - Osthushenrich, Judith (Praxishandbuch Hochschullehre II - Bewertung, Digitalisierung und Barrierefreiheit)
Was macht gelungene Hochschullehre aus? Und an welchen Stellschrauben kann ich drehen, um die eigene Lehre zu verbessern? Das zweibändige "Praxishandbuch Hochschullehre" bietet als Standardwerk Orientierung bei didaktischen Fragen und beleuchtet aktuelle Entwicklungen des Bereichs. In Band II setzen sich die Beiträger:innen mit dem Prüfen und Bewerten von Studierenden auseinander, geben Tipps zu Feedback und Evaluation und widmen sich den Themen Digitalisierung, Nachhaltigkeit sowie Barrierefreiheit. Angereichert mit Abbildungen, Definitionen, Schlagworten, Schritt-für-Schritt-Anleitungen und einem umfangreichen Glossar lädt der anwendungsorientierte Leitfaden alle Lehrenden dazu ein, sich aktiv mit den wesentlichen Inhalten der Hochschullehre auseinanderzusetzen – unabhängig von Fachrichtung und Erfahrungsstufe. utb+: Zusätzlich zum Buch stehen zu einigen Beiträgen hilfreiche Materialien wie Verlaufsprotokolle, Vorbereitungs- und Bewertungsbögen zum Download bereit. Verfügbar in drei Ausgabearten: Print, E-Book (PDF), Web-Book (Buch als Website). Das Web-Book integriert Buchinhalte und digitale Elemente. Für Print und E-Book sind die digitalen Materialien über utb.de kostenlos abrufbar.

Angabe der Auszahlungsbedingungen bei einem Recht zu deren nachträglicher Abänderung. Anmerkung zu BGH, Urt. v. 17. 12. 2024 - XI ZR 314/21 - Bartlitz, David (Entscheidungsanmerkungen zum Wirtschafts- und Bankrecht (WuB))

Weigerung der Gewährleistung der Interoperabilität einer Plattform mit App eines Drittunternehmens. Anmerkung zu EuGH, Urt. v. 25. 2. 2025 - C-233/23 - Bartlitz, David (Europäische Zeitschrift für Wirtschaftsrecht (EuZW))

Integration of multiple-linear and tumbling kinematics into self-piercing riveting - Holtkamp, Pia Katharina; Wituschek, Simon; Lechner, Michael; Meschut, Gerson (MATEC Web of Conferences)
Conventional mechanical joining processes are typically rigid in their tool systems and can only react to changing process and disturbance variables to a limited extent. At the same time, various industries are increasingly trending towards multi-material systems consisting of parts with varying geometric and mechanical properties. Due to the varying properties, rigid mechanical joining processes require sampling procedures and periodic changes of tool components or auxiliary joining parts. Consequently, research is focusing on versatile mechanical joining processes that allow increased control by modifying the process parameters. Two processes based on self-piercing riveting can achieve a significant increase in process influence possibilities through a multi-linear actuator as versatile self-piercing riveting (V-SPR) and a tumbling superimposed actuator as tumbling self-piercing riveting (T-SPR). Initial research into V-SPR has shown that this process can be used to achieve a higher variation in overall package thickness by adapting the rivet geometry and using multiple linear actuators. The T-SPR process also enables increased material flow control by means of targeted compression of the rivet using the tumbling actuator, thereby extending the range of joints that can be manufactured. Based on these two processes, a combination of the two mechanisms of action is to be developed.

Non-destructive testing in versatile joining processes - Lechner, M.; Borgert, Thomas; Busch, Matthias; Harms, A.; Holtkamp, Pia Katharina; Römisch, D.; Wituschek, Simon; Kappe, Fabian (Materials Research Proceedings)
Abstract. Mechanical joints are traditionally analyzed through destructive micrograph analysis, which may compromise internal geometry and morphology, as evidenced by radial cracks in semi-tubular self-pierce riveting. In contrast, industrial X-ray computed tomography (XCT) offers a non-destructive method for component diagnosis, providing volumetric insights without damaging the sample and enabling dimensional measurement. The DFG-funded Collaborative Research Center TRR 285 is exploring XCT's application in assessing mechanical joinability across various joining processes and materials, particularly in multi-material systems like steel-aluminum joints. XCT faces challenges in accurately capturing multi-material compositions, leading to artifacts that complicate interface detection. This research aims to validate XCT for joint investigations, yielding quantitative characteristics that surpass those from traditional micrograph analysis.

Die künstlerische Moderne zu Besuch in Büren. Ein Blick auf die Beziehung von Paula Modersohn-Becker zum westfälischen Künstler Bernhard Hoetger - Schreckenberg, Carolin
Die Arbeiten Paula Modersohn-Beckers sind von weltweiter Berühmtheit. Ihr Werk besticht durch Direktheit und Singularität ihres künstlerischen Ausdrucks. Heute gilt sie als zentrale Wegbereiterin moderner Strömungen in Deutschland. 1 An ihrer künstlerischen Genese zu einer der bedeutendsten Vertreterinnen des frühen Expressionismus ist ein Westfale, der Bildhauer Bernhard Hoetger, nicht unbeteiligt, der ihr zu wichtigen Zeitpunkten ihres kurzen Lebens ein Wegbegleiter war und der sie in das Bürener Land führte. Jene damals von Paula Modersohn-Becker beschrittenen Wege können noch heute verfolgt werden. So zeichnen seit 1998 Schilder und Erläuterungstafeln den Weg am Fluss Alme aus. Vorher sollte es Hoetger und Modersohn-Becker aber in die Kunstkapitale um 1900 führen, nach Paris.

Machine learning of continuous and discrete variational ODEs with convergence guarantee and uncertainty quantification - Offen, Christian (Mathematics of Computation)
The article introduces a method to learn dynamical systems that are governed by Euler–Lagrange equations from data. The method is based on Gaussian process regression and identifies continuous or discrete Lagrangians and is, therefore, structure preserving by design. A rigorous proof of convergence as the distance between observation data points converges to zero and lower bounds for convergence rates are provided. Next to convergence guarantees, the method allows for quantification of model uncertainty, which can provide a basis of adaptive sampling techniques. We provide efficient uncertainty quantification of any observable that is linear in the Lagrangian, including of Hamiltonian functions (energy) and symplectic structures, which is of interest in the context of system identification. The article overcomes major practical and theoretical difficulties related to the ill-posedness of the identification task of (discrete) Lagrangians through a careful design of geometric regularisation strategies and through an exploit of a relation to convex minimisation problems in reproducing kernel Hilbert spaces.